Kebijakan Pendidikan: Perencanaan Pembelajaran Guna Menyikapi Kekerasan Gender Berbasis Online (KGBO) - Khalimatus Sa’diyah; Rahma Puspita Ningrum (Pusat Studi Wanita dan Keluarga UGM, 2022)
The purpose of writing this article is to explain how anti- Online Based-Gender Violance (KGBO) learning planning is applied to students starting from the junior high school level. The Online Based-Gender Violance (KGBO) case that continuous to increase shows that a solustion is needed in dealing with these problems. By involving several parties ranging from teachers, the Education Office and the Integrated Service Center for the Empowerment of Women and Children (P2TP2A), students and parent of students, it can produce good collaboration to implement the proposed education policy. The research method used is descriptive qualitative by using secondary data (library research) from the media, journals, news or books that are relevant and able to answer the problem formulation. Based on the type of qualitative research, there are four stages in analyzing data starting from the process of collecting data, reducing data, presenting data and drawing conclucions. Through these stages it will produce a factual study and findings of the theme raised. The proposed policy that Online Based-Gender Violance (KGBO) learning is taught not only through material but also provides direct opportunities for student to campaign socially and learn to the Education Office and the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) which is expected to become a suggestion that can reduce exixting Online Based-Gender Violance (KGBO) problems.